Stress and productivity in workers of textile companies - Ramos-Galarza, Carlos (2019)
The purpose of this paper is to analyze the relationship between two psychological factors which are occupation stress and productivity, that influence workers immerse into textile production labor context. Design/methodology/approach: This study has a quantitative methodology, is cross-sectional, nonexperimental and with an explicative scope. Findings: The results of this research allow to identify that occupational stress levels cause a negative impact on worker’s productivity in the textile production area. Research limitations/implications: There are two limitations in this study, first is the participant’s subjectivity when filling the questionnaires because it was self-reported and the second limitation is that the sample is specifically from a city of a South American country. Practical implications: The results of this investigation show as an evidence the need for psychological intervention within companies for occupational stress, because it will impact in a negative way the textile production of a company, which will guide future research making possible to develop and apply psychological treatment programs pro employee’s mental health. Social implications: A textile company with low productivity will bring strong economic losses and even bankruptcy, although, thanks to this study it was possible to identify that occupational stress will have a negative impact in productivity, drawing an important based line to future research, looking to improve worker’s performance and hence, companies’ profits contributing to social economic processes. Originality/value: In general, companies of textile industry (as many others from capitalist economic system), make substantial investments in technology instruments, specialized workers, machines’ maintenance and reparation, marketing, etc. to improve their production standards, however, there is a low investment on worker’s mental health, as it has been found in this study it generates a strong negative impact on its productivity.